Betel quid oral lichenoid lesions: a hospital based cross‐sectional study. Issue 1 (29th July 2015) - Arya, Sugandha; Vengal, Manoj; Raju, Bina; Patil, Neelkant; Sathosker, Sujatha; Bateja, Sumit; David, Jamil
Abstract: Objective: The aim of this study was to assess the prevalence and risk indicators of betel quid oral lichenoid lesions in chewers. Methods: A total of 1209 chewers were identified and categorized into three main groups based on the type of lesion: betel quid oral lichenoid lesions only, betel quid oral lichenoid lesions in association with quid‐induced other oral mucosal lesions, and no lesions. Multinomial regression analyses were used to determine associations between dependent and independent variables. Results: Betel quid oral lichenoid lesions were more common in individuals who chewed quid comprising both tobacco and areca nut, and in those who chewed it two to three, or greater than three, times a day. Betel quid oral lichenoid lesions + quid‐induced other oral mucosal lesions were more likely to occur in females, and in individuals who chewed quid containing both tobacco and areca nut, in their processed and unprocessed forms, and greater than three times a day. Conclusion: The prevalence of betel quid oral lichenoid lesions was higher than that reported in previous studies conducted in India. Increase in the frequency and duration of quid chewing was associated with increased likelihood of developing these oral lichenoid lesions.